2019
DOI: 10.1186/s41927-019-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

AxSpA patients who also meet criteria for fibromyalgia: identifying distinct patient clusters using data from a UK national register (BSRBR-AS)

Abstract: Background Around 1 in 8 patients with axial spondyloarthritis (axSpA) also meet criteria for fibromyalgia and such patients have considerable unmet need. Identifying effective therapy is important but to what extent fibromyalgia-like symptoms relate to axSpA disease severity has not been established. The aim of the current analysis was to determine whether distinct clusters of axSpA patients exist and if so to determine a) whether they differ in terms of prevalence of fibromyalgia and b) the feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…This is not surprising, as results from previous studies have shown that axSpA patients with concomitant fibromyalgia have more disease activity, functional impairment, fatigue, pain, and poorer quality of life than patients without fibromyalgia [ 37 , 38 ]. Studies have also found that high axSpA disease activity and widespread pain are associated with the development of fibromyalgia [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as results from previous studies have shown that axSpA patients with concomitant fibromyalgia have more disease activity, functional impairment, fatigue, pain, and poorer quality of life than patients without fibromyalgia [ 37 , 38 ]. Studies have also found that high axSpA disease activity and widespread pain are associated with the development of fibromyalgia [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Starting on a TNFi is associated with recovering from FM. The coexistence of FM in patients with axSpA has previously been found to be associated with high levels of axSpA disease activity in cross-sectional studies [ 16 , 17 ]. The current study adds to this body of knowledge by providing evidence that while high levels of axSpA disease activity are associated with future FM development, low levels of axSpA disease activity are associated with recovery from FM.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence is even higher in people with inflammatory musculoskeletal conditions; for example, patients with rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis have been shown in a meta-analysis to have prevalence proportions of 21%, 18%, and 13%, respectively (4). The diagnosis of fibromyalgia can be particularly challenging when the clinical features (such as pain, fatigue, and tenderness on palpation) are shared with the coexisting condition (5).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence is even higher in people with inflammatory musculoskeletal conditions; for example, patients with rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis have been shown in a meta‐analysis to have prevalence proportions of 21%, 18%, and 13%, respectively (4). The diagnosis of fibromyalgia can be particularly challenging when the clinical features (such as pain, fatigue, and tenderness on palpation) are shared with the coexisting condition (5).
People whose symptoms meet the criteria for fibromyalgia have symptoms whose impact is very similar to those who have received a fibromyalgia diagnosis. The impact of symptoms in people who meet the criteria for fibromyalgia (or who have received a diagnosis) is much greater than in people with chronic pain. The diagnosis of fibromyalgia may be overlooked in men. Particular attention needs to be paid for improving work outcomes in those with fibromyalgia symptoms/diagnosis.
…”
Section: Introductionmentioning
confidence: 99%